TikTok affordances and everyday nationalism : An exploration of #expat - Larvik, Georgia (2023)
Although we often speak of a highly interconnected and globalized world, imagining the world as being comprised of nations is a pervasive and often more commonplace than we tend to notice in our everyday lives. Nationalism is often associated with political unrest, but indeed, constructing the world as naturally being composed of nations can be conceptualized as its own form of nationalism: this is what Michael Billig refers to as ’banal nationalism.’ Iden-tifying this discourse and understanding how it is constructed is important, as it allows us to not only recognize this idea of a world of nations, but to look past it to examine what it may be obscuring in the process. In this research, I choose TikTok as a site for investigating constructions of banal nationalism under #expat. Today, social media is an important site for the co-creation of everyday discourse, and a place where it is possible to observe the evolution of popular narratives over time. In 2023, TikTok currently occupies a place as one of the most popular sites for user generated content, and the platform’s array of affordances make video content creation accessible to a wide audience. Therefore, it is necessary to understand the interplay between platform affordances, construction of narratives, and their relationship with banal nationalism. Drawing on Michael Billig’s theory of banal nationalism and more recent reworkings of the concept, I employ methods from Alexandra Georgakopoulou’s small stories research on social media and adapt them to TikTok. This research aims to understand how everyday nationalism is constructed on Tiktok, how Tiktok’s affordances contribute to how it is constructed, and finally, how the identities of creators are constructed in this media, by exploring #expat. In collecting 100 of the most popular videos under #expat, I explore common narrative frameworks in order to create a typology and illustrate the ways in which the nation is indexed within these frameworks. My analysis is qualitative and draws from narrative analysis, visual analysis and multimodal discourse analysis. The results of this demonstrate that several common narrative frameworks can be found under #expat, and that storytelling devices common to small stories on social media, including narrative-stancetaking and the construction of identity not only as the principal storyteller, but as a member of a particular nationality, regularly reinforce the idea of a world of nations. Furthermore, the identities constructed under this hashtag, along with the common narrative subjects, tend to center around highly positive appraisals of the destination country, with very few visible critical stances. This research has limitations and would benefit from further exploration of content on TikTok, an investigation of popular creators, and more in-depth analysis of the ideologies that are present in the content.